A HOLISTIC APPROACH TO THE FORMATION OF VOCALISTS OF PERFORMING CULTURE (Web of Teachers: Inderscience Research, 2024)
The article examines the problem of forming the performing culture of pop vocalists, the importance of the integrative approach in training pop vocalists is substantiated. Providing integrative content educational disciplines is associated not only with the study of vocal performance, but also with familiarization with artistic creative activity, which manifests itself in classes in other musical disciplines, dance, fundamentals stage movement, etc. The author characterized the concept of “performing culture of pop vocalists” as the totality of the technical and artistic-figurative aspects of the performed works, which carries traditions and innovations in the interpretation of the idea of the composer's plan, the style and genre of compositions, their form and content, revealing creative potential of the student’s personality at the level of aesthetic consciousness and aesthetic activity, performing skills and abilities combined with experience in public speaking. The author identified the structure of performing culture pop vocalists, which includes the following components: professionally important qualities, individual qualities, stage culture, emotional and psychological preparation. Professionally important qualities ensure future successful professional activities of pop vocalists. Individual qualities are formed in conditions of active cognitive activity, musical practice, interpretation of musical and artistic values. They develop in the process of various types of musical and cognitive activities, pop vocalists, which involves the perception of music and its performance. An important aspect of stage culture pop vocalists is the culture of sound - this is the tone that creates the mood and conveys depth, brightness and content of performance. One of the indicators of stage culture is the image of the performer, which reflects the inner world of both the artist himself and his image, conveyed by various types of stage embodiment of the artistic image of the performed work. A vivid stage embodiment of a musical image requires emotional and psychological preparation. In many ways, the reaction to a stage situation depends not only on past experience and skill of the artist, but also on his way of reacting to factors causing stress, resistance emotional exhaustion. The formation of a performing culture based on an integrative approach is the process of synthesis of academic disciplines, creative development, vocal training, formation of performance technique, and also the use of diverse creative forms of training, helping to increase the level of readiness of pop performers vocalists for future professional activities.